Secondhand Tobacco Smoke Exposure and Neuromotor Function in Rural Children - Yeramaneni, Samrat (J Pediatr, 2015)
OBJECTIVES: To investigate the relationship between secondhand tobacco smoke (SHS) exposure and neuromotor function in children. STUDY DESIGN: We studied 404 children aged 7–9 years who were exposed to SHS and other environmental neurotoxicants. Parent reported smoking habits, and serum cotinine levels were measured in children to determine SHS exposure. Halstead-Reitan Finger Oscillation Test (HRFOT), Purdue Grooved Pegboard Test – Kiddie version (PGPT), and Bruininks-Oseretsky Test of Motor Proficiency 2-Short form (BOT-2) were used to assess neuromotor function. Multivariable regression models that accounted for potential confounders were used to evaluate the associations. RESULTS: Approximately 50% of the children were exposed to SHS based on serum cotinine measures. Exposure to SHS was significantly associated with motor impairment in children, including diminished visuo-motor coordination (p=0.01), fine motor integration (p=0.01), balance (p=0.02), and strength (p=0.04) after adjusting for exposures to lead and manganese, age, sex, body mass index, measures of cognitive abilities of parents, parental education, and quality of home environment CONCLUSIONS: We conclude that SHS is a neurotoxicant that may be associated with impaired childhood neuromotor function.